Question: Find the equation of the line joining $\displaystyle (0-3)$, $\displaystyle (-5,0)$

I encountered a problem when finding the gradient. y2-y1/x2-x1

If $\displaystyle (0, -3)$ is the x1,y1

$\displaystyle 0-(-3)/-5-0$ = $\displaystyle 3/-5$ = $\displaystyle -0.6$

If $\displaystyle (0, -3)$ is the x2,y2

$\displaystyle -3-0/0-5$ = $\displaystyle -3/-5$ = $\displaystyle 0.6$

Where am I wrong? [Solved]

My workings for this question:

Gradient = y2-y1/x2-x1

$\displaystyle =$ $\displaystyle (-3-0)/(0-(-5)$

$\displaystyle =$ $\displaystyle -3/5$

$\displaystyle =$$\displaystyle -0.6$

$\displaystyle 0=-0.6(-5)+b$

$\displaystyle 0=3+b$

$\displaystyle 0-3=3-3+b$

$\displaystyle -3=b$

Therefore, $\displaystyle y=-0.6x-3$

Is my answer correct?